Green Politics: The Rise of Environmental Political Movements - Dr Farhat Nasim; Dr Qamar-un-Nisa (Journal of Religion and Society, 2025)
This paper explores the emergence and evolution of green politics as a global phenomenon rooted in the growing awareness of environmental crises and the corresponding rise of environmental political movements. It traces the historical development of green ideologies from early grassroots activism in the 1960s and 1970s to more structured political expressions such as green parties and transnational advocacy networks. Green politics, as an interdisciplinary field, integrates ecological concerns with demands for social justice, sustainable development, and systemic transformation of political and economic structures. The study emphasizes the significance of climate justice, environmental racism, and indigenous environmentalism in shaping modern environmental discourses. It further investigates the interplay between globalization, technology, and green activism, illustrating how social media and green technology have amplified environmental advocacy and youth-led movements like Fridays for Future. The paper also highlights the challenges faced by environmental movements, including state surveillance, political resistance, limited funding, and negative media portrayal. Through case studies of successful environmental campaigns and anti-nuclear protests, it showcases the potential of organized resistance in influencing policy and public opinion. The analysis underscores the pressing need for institutional reforms, inclusive governance, and international cooperation to address ecological degradation. Ultimately, the rise of green politics signifies a paradigm shift toward rethinking political priorities, where environmental sustainability is central to global justice and democratic accountability. Keywords: Green Politics, Environmental Movements, Climate Justice, Sustainability, Environmental Activism, Social Justice, Globalization, Environmental Policy, Youth Activism, Ecological Governance